Role of Technological Knowledge and Entrepreneurial Orientation on Entrepreneurial Success: A Mediating Role of Psychological Capital - Ardelean, Ben-Oni (Frontiers in Psychology, 2021)
This study pursues to build the conceptual model of entrepreneurial success that discusses the concept and phenomenon of entrepreneurial success and its perquisites and outcomes. This proposed mode anticipated that factors technological knowledge, entrepreneurial orientation, and psychological knowledge influence entrepreneurial success. This paper explains previous literature on perquisites, the phenomenon of technological knowledge, entrepreneurial orientation and psychological knowledge, and entrepreneurial success. This conceptual paper targets the scholarly works that provide support for the proposed model. A significant contribution of this paper is to propose an original relationship between prerequisites, phenomena, and consequences in entrepreneurial success. The proposed model shows a novel conceptualization of how these constructs may be connected to affect entrepreneurial success outcomes. This study enhances the literature by providing the theoretical literature of forerunners and outcomes for entrepreneurial success. In addition, this study has important implications for practitioners and entrepreneurs to generate success in entrepreneurial activities. Based on new insights, this study also developed and suggested new approaches and opportunities for future research.